Analyzing Attention to Scandal on Twitter: Elites Sell What Supporters Buy. (June 2023) - Warner, Seth B.
Scandal has been described as socially constructed, in that some combination of the public, the media, and the political elite agrees that a transgression has occurred. This study is among the first to directly observe the "scandal as a construct" premise, using time-series data to estimate how each group's attention to scandal affects that of every other. These data, collected from Twitter byBarberá et al. (2019), measure the daily tweet volume of media outlets, Members of Congress, and samples of the public in relation to four Obama Administration scandals. Granger causality testing and impulse response functions show, as expected, that a jump in scandal-related tweets by one group affects the tweet volume of every other. But the groups wield unequal influence. Over the long-run, elites drive their supporters' attention to scandal more than vice-versa. However, in two of the four scandals, the opposite effect was seen in the short-run, opening the possibility of a "sounding board" effect where elites are responsive to the initial reactions of their supporters but lead the conversation thereafter. These results encourage further study into how short- and long-term information flows differ, and why groups may lead in some issue areas but follow in others.